Mesoscale Advective and Biological Processes Alter Carbon Uptake Capacity in a Shelf Sea - Macovei, Vlad A.; Callies, Ulrich; Calil, Paulo H. R.; Voynova, Yoana G. (Frontiers in Marine Science, 2022)
Marine uptake of carbon dioxide reduces the accumulation of carbon dioxide in the atmosphere. Continental shelf seas are essential for carbon uptake from the atmosphere, but are also highly variable environments, for which uncertainties of carbon budget estimates are large. Recent studies indicate that their carbon sink capacity is weakening. A way to reduce the uncertainty of carbon budgets is to increase our observational capacity, for example through FerryBox installations on Ships-of-Opportunity. Here, we compare FerryBox observations in the North Sea for the fall seasons of 2019 and 2020. We show that short-lived mesoscale events can be characterized when the sampling resolution is adequately high, and that these events cause changes in essential environmental variables on the same magnitude as seasonal cycles. Whether advective or biological in origin, these events rapidly lowered seawater pCO2 by 8–10% and influenced the carbon uptake capacity. We demonstrate the importance of resolving and integrating the variability of these smaller features in regional carbon budget assessments and advocate for the tuning of models in order to capture this small-scale variability.